(untitled) (Revista Direito em Debate, 2020)
Over the past forty years, the Waimiri-Atroari indigenous people have been blocking daily access at night to the stretch of highway BR-174 that cuts through their territory, between the states of Amazonas and Roraima, while the government, reinforced by the current speech in the federal government, tries to find ways to abolish the practice. Through deductive study, this research will start from a historical contextualization of the impacts of the construction of the road on the indigenous people, based on a colonialist policy of extermination, to then describe the problem as it persists in the present. Subsequently, the study addresses the plexus of constitutional rights guaranteed to indigenous peoples, such as permanent tenure and exclusive enjoyment for their own development and protection of traditionally occupied lands. Then, it approaches the possibility of State intervention on indigenous territory, as a measure of economic development, provided that the set of fundamental rights is observed, including prior, free and informed consultation of the indigenous people to be affected. Finally, the work shows that lowering and stigmatizing treatment of indigenous peoples by the Government is no longer tolerated by the current law, which abandoned any colonialist bias. State intervention that may limit indigenous territorial law must observe prior consultation and ensure effective intercultural dialogue, so that the affected people can take a leading role in the decision-making process regarding the issue of road blockage.